Effects of pomegranate juice supplementation on oxidative stress biomarkers following weightlifting exercise - Ammar, A.; Turki, M.; Hammouda, O.; Chtourou, H.; Trabelsi, K.; Bouaziz, M.; Abdelkarim, O.; Hoekelmann, A.; Ayadi, F.; Souissi, N.; Bailey, S. J.; Driss, T.; et al. (Nutrients, 2017)
The aim of this study was to test the hypothesis that pomegranate juice supplementation would blunt acute and delayed oxidative stress responses after a weightlifting training session. Nine elite weightlifters (21.0 ± 1 years) performed two Olympic-Weightlifting sessions after ingesting either the placebo or pomegranate juice supplements. Venous blood samples were collected at rest and 3 min and 48 h after each session. Compared to the placebo condition, pomegranate juice supplementation attenuated the increase in malondialdehyde (-12.5%; p < 0.01) and enhanced the enzymatic (+8.6% for catalase and +6.8% for glutathione peroxidase; p < 0.05) and non-enzymatic (+12.6% for uric acid and +5.7% for total bilirubin; p < 0.01) antioxidant responses shortly (3 min) after completion of the training session. Additionally, during the 48 h recovery period, pomegranate juice supplementation accelerated (p < 0.05) the recovery kinetics of the malondialdehyde (5.6%) and the enzymatic antioxidant defenses compared to the placebo condition (9 to 10%). In conclusion, supplementation with pomegranate juice has the potential to attenuate oxidative stress by enhancing antioxidant responses assessed acutely and up to 48 h following an intensive weightlifting training session. Therefore, elite weightlifters might benefit from blunted oxidative stress responses following intensive weightlifting sessions, which could have implications for recovery between training sessions.